The marketization of public discourse: The Chinese universities. (February 2014) - Han, Zhengrui
Contemporary universities are characteristic of an evident proliferation of corporate discourse. A sole concentration on the production of new knowledge and the education of students does not ensure the prosperity or even survival of universities any longer, and equally important are the admission of elite students, the outcome-based evaluation of academic performance, the establishment of alumni network and also fundraising. This article examines how and to what extent this trend of marketization has invaded the order of discourse of Chinese universities. The research methodology combines the paradigms of critical discourse analysis (CDA) and the tenets of critical genre analysis [Bhatia VK (2007) Towards critical genre analysis. In: Bhatia VK, Flowerdew J and Jones RH (eds) Advances in Discourse Studies . London: Routledge, pp. 166–177], with particular attention paid to the notion of genre, interdiscursivity and conversationalization. The texts examined include ceremonial speeches, regulatory documents, insiders' accounts and field notes. Analytical results show that the trend of marketization, in spite of a potential threat for academic integrity, does facilitate the institutional restructuring and transformation of universities in the context of Mainland China.